Thermally activated delayed fluorescence and high-contrast mechanochromism of anthrone-based donor–acceptor systems - Sudhakar, Pagidi; Slawin, Alexandra; Zysman-Colman, Eli (Frontiers in Chemistry, 2023)
The development of materials that emit in the deep-red to near-infrared region of the spectrum has attracted significant attention due to their potential as optical sensing and imaging reagents in biology. Herein, we report the synthesis and optoelectronic characterization of four anthraquinone-based emitters, T-tBuCz-AQ, T-MeOCz-AQ, C-tBuCz-AQ, and C-MeOCz-AQ, and two pyrazoloanthrone-based emitters, tBuCz-PA and DMAC-PA. Depending on the donor, these compounds emit in the spectral range between 640 and 750 nm in the neat film, while the emission of the 10 wt% doped films in poly(methyl methacrylate) (PMMA) is blue-shifted between 600 and 700 nm and has low photoluminescence quantum yields between 2.6% and 6.6%. Of these compounds, T-tBuCz-AQ, T-MeOCz-AQ, and C-tBuCz-AQ exhibited thermally activated delayed fluorescence (TADF) in 10 wt% doped films in PMMA, while the crystals of T-tBuCz-AQ also showed TADF. Compound tBuCz-PA showed a high-contrast and reversible photoluminescence (PL) response upon mechanical grinding and hexane fuming.